The Use of Color Gradation on Program Visualization for Learning Programming - Rossevine Artha Nathasya; Oscar Karnalim (IJNMT (International Journal of New Media Technology), 2019)
According to several works, Program Visualization (PV) enhances student understanding further about how a particular program works. However, to our knowledge, no PVs utilize color gradation as a part of their features, even though color plays an important role in visualization. Therefore, two uses of color gradation on PV are proposed on this paper. On the one hand, color gradation can be used to display execution frequency of each instruction; instruction with higher execution frequency will be assigned with more-prominent color. Such piece of information is expected to help student for understanding program complexity. On the other hand, color gradation can also be used to display access frequency of each variable; variable with higher access frequency will be assigned with more-prominent color. Such piece of information is expected to help student for understanding program-to-variable dependency. Both uses are proved to be effective for learning programming according to our evaluation. Index Terms—program visualization, color gradation, program complexity, program-to-variable dependency, computer science education